"The end of Europe" (and of what is not Europe). Motifs and Versions of the Ending According to Rafael Spregelburd (Anclajes, 2022)
In the last decades, catastrophes and complexities of history appear in Rafael Spregelburd´s theater not only in its thematizations, but also in intermedial, serial and long-lasting explorations that seek to mobilize, to our understanding, a thought and a practice about the place of artistic (and political) imagination today. It also operates with the recycling of multiple materials and a critical rework about fiction, reality and time that connect it with a way of understanding history as “preposterous history” (Bal). The present work seeks to analyze his most recent project, The End of Europe, written between 2012 and 2017, under the following premise: a theater in times of crisis, calamities and endings seeks to dismantle the stories of the end making it seem that the point that marks the hatching is not so much a closure, but a possibility to understand and inhabit the world in another way, even if we still do not know how to do it.
Keywords: The end of Europe; Rafael Spregelburd; argentine theatre; theatre series; long-running